Caracterización de especies rastreras arvenses con tolerancia a sequía y uso potencial como cobertura del suelo - Macías Guadamud, Angelica Yomira (2024)
The objective of the research was to characterize creeping weed species with tolerance to drought and potential use as ground cover. Four weed species present in the Carrizal River valley were evaluated. The species evaluated were Centrosema pubescens, Macroptilium atropurpureum, Tridax procumbens and Distimake quinquefolius. A randomized complete block design was used with four treatments, five repetitions and 20 experimental units. The experimental unit was made up of 9 m2 plots. Physiological variables such as effective quantum yield (ΦPSII), maximum quantum efficiency (Fv/Fm), electron transport rate (ETR), percentage of ground cover (PGC), relative leaf water content (RWC), specific leaf area (ELS), specific leaf weight (ELW), dry mass accumulation (DMA), daily growth rate (DGR) and soil water content (SWC). The majority of variables analyzed were significantly influenced (p<0.05) by the weed species evaluated, where the Tridax procumbens species stood out with the highest averages. All the weeds evaluated were drought tolerant, they managed to maintain a photochemical activity (ΦPSII, Fv/Fm and ETR) high enough to not fall into photo-inhibition and damage to the photosynthetic apparatus due to drought. Likewise, the four species studied achieved a high growth rate, soil cover and great capacity to retain soil moisture. The results suggest that the four weed species can be used as cover crops for soil protection and conservation purposes.